Sleuthing machine - Bowling, Dusti (Bowling, Dusti. Aven Green, 2021)
"Third-grader Aven Green has been solving mysteries for a whole month, cracking such cases as The Mystery of the Cranky Mom. But can this perceptive detective solve two cases at the same time? First her teacher's lunch bag disappears. Then Aven's great-grandma's dog goes missing. Fortunately, since Aven was born without arms, all the "arm" cells went to her super-powered brain instead. (That's her theory.)"--